(untitled) (Research, Society and Development, 2021)
The text aims to discuss the behavior of Brazilians regarding the practice of eating in times of coronavirus pandemic. The study seeks to analyze how food was resignified due to the social isolation suggested by the World Health Organization (WHO) and the Pan American Health Organization (PAHO) and adopted by some states of the federation. From the netnographic observation we verified how the delivery service, through digital media, has become a communication link between consumers and entrepreneurs, to maintain active commercial activities, requiring in this crisis greater attention to hygienic practices in the preparation and delivery of products. For food service companies that did not have a strong track record, this mode of delivery contributed to the survival of the enterprises. In general, we were able to evaluate how feeding practices anchored in digital tools in times of social remoteness, assumed a cultural, economic and technological symbolism, in order to cope with the pandemic outbreak of coronavirus.